Design and Synthesis of Isoxazole Derivatives: Evaluating Their Antituberculosis Activity through Experimental and Docking Studies - Jisha Annie Geevarghese (International Journal of Medical Toxicology and Legal Medicine, 2024)
The resurgence of tuberculosis (TB) as a major global health concern, driven by multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains of Mycobacterium tuberculosis (Mtb), underscores the need for new therapeutic agents. This study focuses on the design, synthesis, and evaluation of isoxazole derivatives for their antituberculosis activity. Using a combination of experimental assays and molecular docking studies, we assessed the potential of these compounds as effective TB treatments. Tuberculosis remains a leading cause of death worldwide, with treatment challenges exacerbated by the rise of MDR and XDR Mtb strains, highlighting the critical need for new antituberculosis drugs. Isoxazole derivatives, known for their diverse biological activities, offer a promising scaffold for the development of new TB therapies. This study aims to design, synthesize, and evaluate isoxazole derivatives for their potential antituberculosis properties, combining experimental assays and molecular docking studies to understand their mechanisms of action. Aromatic aldehydes, hydroxylamine hydrochloride, and sodium acetate were reacted in ethanol under reflux to synthesize isoxazole derivatives. The compounds were purified and confirmed by NMR and MS analysis. The minimum inhibitory concentration (MIC) of the synthesized compounds was determined using the microdilution method against Mtb H37Rv. Compounds were diluted in Middlebrook 7H9 broth, and Mtb cultures were incubated to identify the lowest concentration inhibiting visible bacterial growth. Using AutoDock Vina and PyMOL, docking studies were performed on the enoyl-acyl carrier protein reductase (InhA) of Mtb. The synthesis yielded isoxazole derivatives with 70%-85% efficiency. Several compounds showed significant antituberculosis activity, with MIC values ranging from 1-8 µg/mL. Notably, compound 3a exhibited the highest activity with an MIC of 1 µg/mL. Docking studies revealed strong binding interactions between the derivatives and the InhA enzyme, correlating well with the observed antituberculosis activity and suggesting inhibition of InhA as a likely mechanism of action. The isoxazole derivatives synthesized in this study demonstrated promising antituberculosis activity. Experimental assays and molecular docking studies indicated strong potential for these compounds as new TB treatments, particularly through the inhibition of the InhA enzyme, warranting further optimization and in vivo studies to advance these compounds toward clinical development.